Biomechanical analysis of the voice and perception of vocal competence as tools for the detection of vocal difficulties in students and teachers of university and vocal performance - García Escudero, Fernando; Gutiérrez Fonseca, Raimundo; Rodríguez Caravaca, Gil; Fernández-Baillo y Rodríguez de Sacristana, Roberto; Gonzalez Diaz, Alba; Durán Poveda, Manuel (Revista de Investigación en Logopedia, 2024)
The oral communicative demand increases daily in the exercise of work functions in which the voice is necessary for the performance of daily work. Teachers, singers, actors, teleoperators, communicators, ticket-takers, health workers, among other professions, are subjected to a very high vocal load as they use their voice at high intensity for long periods of time, presenting a greater predisposition and incidence of developing vocal pathology. The aim of the present study is to analyse the differences in vocal difficulties between an Arts Education group (GE-A) and a Non-Arts Education group (GE-NA) using a screening procedure based on biomechanical voice analysis combined with the VHI-10 vocal disability questionnaire. The hypothesis suggests that participants in the GE-A group present a greater degree of functional alteration than those in the GE-NA group, due to the daily overload generated due to the high vocal demand inherent to the speciality. A total of 182 participants, 80 men and 102 women, were studied. The data from the screening by biomechanical analysis of the vocal folds reveal a profile with a greater imbalance in the dynamics of the vocal folds during phonation in the GE-A. These results could be associated with a higher vocal demand in GE-A and would justify the implementation of periodic diagnostic and preventive measures, as well as specific speech therapy rehabilitation treatments in this group.